Temperature determination of the pre-polarising process of an earth's magnetic field MRI system. (June 2019) - Solis-Najera, S E; Vazquez, F; Martin, R; Rodriguez, A O; Medina, L
Abstract: Magnetic resonance imaging is a low inherent sensitivity technique with a low nuclear polarisation at thermal equilibrium. Low sensitivity is a major problem for ultralow field magnetic resonance imaging, but it can be overcome by improving the polarising process. This procedure may increase the temperature of the sample to be imaged affecting its integrity. We investigate the temperature increase generated by a pre-polarisation process for an ultralow field nuclear magnetic resonance system. We measured the pre-polarising field with a magnetic field sensor inside the system to study the possible effects on it. Temperature readings inside the system were also obtained varying the polarising time. A linear fitting was then calculated showing a low rate of 0.0086°C/s, and a total increment of 5°C for around 10 minutes. This is an important temperature increment that it should be considered when running imaging experiments of biological subjects.